Effects of Cholinergic Stimulation with Pyridostigmine Bromide on Chronic Chagasic Cardiomyopathic Mice. (21st August 2014) - Cuba, Marília Beatriz de; Ribeiro Machado, Marcus Paulo; Farnesi, Thais Soares; Alves, Angelica Cristina; Martins, Livia Alves; Oliveira, Lucas Felipe de; Capitelli, Caroline Santos; Leite, Camila Ferreira; Vinícius Silva, Marcos; Machado, Juliana Reis; Kappel, Henrique Borges; Sales de Campos, Helioswilton; et al.
Abstract : The aim of the present study was to assess the effects of an anticholinesterase agent, pyridostigmine bromide (Pyrido), on experimental chronic Chagas heart disease in mice. To this end, male C57BL/6J mice noninfected (control:Con) or chronically infected (5 months) with Trypanosoma cruzi (chagasic:Chg) were treated or not (NT) with Pyrido for one month. At the end of this period, electrocardiogram (ECG); cardiac autonomic function; heart histopathology; serum cytokines; and the presence of blood and tissue parasites by means of immunohistochemistry and PCR were assessed. In NT-Chg mice, significant changes in the electrocardiographic, autonomic, and cardiac histopathological profiles were observed confirming a chronic inflammatory response. Treatment with Pyrido in Chagasic mice caused a significant reduction of myocardial inflammatory infiltration, fibrosis, and hypertrophy, which was accompanied by a decrease in serum levels of IFN γ with no change in IL-10 levels, suggesting a shift of immune response toward an anti-inflammatory profile. Lower nondifferent numbers of parasite DNA copies were observed in both treated and nontreated chagasic mice. In conclusion, our findings confirm the marked neuroimmunomodulatory role played by the parasympathetic autonomic nervous system in the evolution of the inflammatory-immune response to T. cruzi during experimental chronic Chagas heart disease in mice.